2013
DOI: 10.1021/cm4023387
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Alkoxysilyl Groups for the Creation of Structurally Controlled Siloxane-Based Nanomaterials

Abstract: Silica-based materials have found many applications in various fields. Alkoxysilanes have been most widely used as precursors. Fine structural control of silica-based materials has become increasingly important for tuning their properties and for developing new functions. In this perspective, utilization of alkoxysilyl groups has been reviewed from the viewpoint of designing siloxane-based nanomaterials. Alkoxy groups have generally been used only as eliminating groups in the sol−gel processing; however, recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 79 publications
0
78
0
1
Order By: Relevance
“…are suitable for a large variety of further reactions (both HSG and NHSG condensations [29,118], hydrosilylation, co-polymerization, etc.) and therefore are very useful building blocks for the synthesis of structured silica-based materials [119]. Importantly, it was shown that these precursors can be reacted selectively and in a controlled way [117,118].…”
Section: Siloxanes By Nhsg Condensations Piers-rubinsztajn Reactionmentioning
confidence: 99%
“…are suitable for a large variety of further reactions (both HSG and NHSG condensations [29,118], hydrosilylation, co-polymerization, etc.) and therefore are very useful building blocks for the synthesis of structured silica-based materials [119]. Importantly, it was shown that these precursors can be reacted selectively and in a controlled way [117,118].…”
Section: Siloxanes By Nhsg Condensations Piers-rubinsztajn Reactionmentioning
confidence: 99%
“…A wide variety of polyhedral oligomeric silsesquioxane (POSS)-based functional materials have been developed using ionic species. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] We recently reported the synthesis of POSS-based ILs, and we investigated their thermal properties. 25,26 By tethering multiple ion pairs composed of imidazolium cations and carboxylates to the vertices of POSS cores or by simply adding POSS molecules with acid groups, the melting temperatures of the ion pairs decreased and their thermal stabilities increased.…”
Section: Introductionmentioning
confidence: 99%
“…14−19 Hybrid Sibased xerogels are of particular interest because they are inexpensive and readily prepared by sol−gel processing, 20 they are heavily cross-linked, and the films can be covalently bonded to naturally stable metal oxide surfaces. 21 In addition, xerogel chemistry and topography can be adjusted by controlling substitution at the −R′ group on the (OR) 3 Si−R′ precursor(s) and the precursor molar ratios, 22 allowing one to form materials that combine the benefits of physically engineered and amphiphilic materials (vide supra). 15,19 While the AF properties and efficacy of hybrid xerogel coatings have been established in field studies, their characterization has lagged, relying primarily on atomic force microscopy (AFM) and Fourier transform infrared (FTIR) microscopy.…”
Section: ■ Introductionmentioning
confidence: 99%